2009
DOI: 10.1038/jid.2009.183
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus in Cutaneous Squamous Cell Carcinoma of Immunocompetent Individuals

Abstract: Squamous cell carcinoma (SCC) is the second most frequently diagnosed skin cancer. It has a higher incidence in immunosuppressed individuals such as organ transplant recipients and human immunodeficiency virus (HIV) carriers. Recently, a newly described polyoma virus, Merkel cell polyomavirus (MCPyV), was found in Merkel cell carcinoma (MCC), a rare aggressive skin cancer also associated with immunosuppression. We hypothesized that MCPyV would be present in SCCs. To test for the presence of MCPyV in immunocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 21 publications
3
92
3
Order By: Relevance
“…It has also been reported that low levels of MCPyV sequence can be amplified from many human tissues where it may undergo low-level replication or latency (1,39,43,44). MCPyV DNA has also been detected in the oral cavity, with prevalence ranging from 8% to as high as 60% (34,35,39). The sensitivity of the detection of MCPyV DNA is affected by variations in the number of cells present in different samples.…”
Section: Detection Of the Viral Genomementioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that low levels of MCPyV sequence can be amplified from many human tissues where it may undergo low-level replication or latency (1,39,43,44). MCPyV DNA has also been detected in the oral cavity, with prevalence ranging from 8% to as high as 60% (34,35,39). The sensitivity of the detection of MCPyV DNA is affected by variations in the number of cells present in different samples.…”
Section: Detection Of the Viral Genomementioning
confidence: 99%
“…MCPyV DNA has been detected at varying levels of frequency (0-100%) in skin samples, and in anal and penile swabs (1,9,20,21,26,(32)(33)(34)(35)(36)(37)(38). The MCPyV viral load on the skin surface varies from less than 1 copy per 1000 cells to 1000 copies per cell (9,26,30,(39)(40)(41).…”
Section: Detection Of the Viral Genomementioning
confidence: 99%
“…MCPyV has been detected in MCC patients and appears to play a key role in tumourigenesis; ~80% of MCCs harbour MCPyV (1). Using quantitative polymerase chain reaction (qPCR), MCPyV has been detected in malignant and benign tumours (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Moreover, certain investigators have reported that low viral loads of MCPyV have also been detected in normal human tissue samples, including skin, liver and respiratory secretions, suggesting that this virus is widespread in the human body (7,17).…”
Section: Introductionmentioning
confidence: 99%
“…Falchook and colleagues (2013) [16] reported the presence of HPVMCPyV in a SCC from a patient with melanoma treated with the BRAF inhibitor dabrafenib. In another study involving SCC, Dworkin and colleagues (2009) [13] demonstrated a higher proportion of HPV DNA among the MCPyV-positive group (87%) in comparison to the MCPyV-negative group (57%), although a clear correlation between these two viruses could not be established. Mittledorf and colleagues (2012) [17] reported HPV6 and MCPyV DNA in a combined MCCinvasive SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, non-melanoma skin cancers have been studied, especially squamous cell carcinoma and basal cell carcinoma. The prevalence of MCPyV in SCC ranges from 13% to 38% [13][14][15].…”
Section: Discussionmentioning
confidence: 99%